The musical-rhythmic intelligence (Journal of Parents and Teachers, 2013)
This section of the magazine that studies the multiple intelligences, is centered in this number on the musical-rhythmic intelligence.The author explains the different developmental phases of this intelligence and he purposes activities that promote its development directly or through other areas of knowledge.
Keywords: Multiple intelligences. Musical-rhythmic intelligence. Activities; education and centerfold